2010
DOI: 10.2118/141168-pa
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Calcium Sulfate and Strontium Sulfate Scale in Waterflood

Abstract: One of the most common methods of preventing downhole and topside mineral-scale formation in oil fields is through the use of chemical-scale inhibitors. Several aspects of the brine composition may affect the performance of the various scale inhibitors used in oilfield applications. This study was conducted to investigate the permeability reduction caused by deposition of calcium sulfate (CaSO 4 ) and strontium sulfate (SrSO 4 ) in Malaysian sandstone and Berea cores from mixing injected Malaysian seawaters (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Moreover, the study also highlighted smaller sized layered platelets, which were attributed to bentonite clay. The larger particles in dry oily petroleum sludge are suggested to be barite, calcite, sandstone, and quartz, which were demonstrated by the findings from other studies, performed by Wang et al (2012) and Bin Merdhah (2010). Another research group presented different minerals content in petroleum sludge by X-ray diffraction (XRD) and attenuated total reflectance–Fourier transform infrared (ATR-FTIR) analysis.…”
Section: Introductionmentioning
confidence: 82%
“…Moreover, the study also highlighted smaller sized layered platelets, which were attributed to bentonite clay. The larger particles in dry oily petroleum sludge are suggested to be barite, calcite, sandstone, and quartz, which were demonstrated by the findings from other studies, performed by Wang et al (2012) and Bin Merdhah (2010). Another research group presented different minerals content in petroleum sludge by X-ray diffraction (XRD) and attenuated total reflectance–Fourier transform infrared (ATR-FTIR) analysis.…”
Section: Introductionmentioning
confidence: 82%
“…They should be nontoxic, biodegradable, and environmentally friendly. Several works have been reported in the literature on developing green scale inhibitors [1][2][3][4][5][6][7][103][104][105][106][107]. Znini et al [144] reported the environmentally friendly scale inhibitors for the scaling activity of steel in H 2 SO 4 using purified compounds and essential oils, which can be achieved from plant extracts.…”
Section: Significance Of Green Scale Inhibitorsmentioning
confidence: 99%
“…Scale inhibitors can circularize the insoluble inorganic salts, prevent scale deposition on the metal surface, which slows down the corrosion rate, and maintains proper heat transfer effect of the equipment. These inhibitors are considered a particular class of chemicals, which are also used to slow or stop scale development in water frameworks [1][2][3][4][5]. Researchers also studied different types of scales and methods to prevent them from using scale inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the extensive use of water injection for oil displacement and pressure maintenance in oilfields, many reservoirs experience the problem of scale deposition when water injection starts. In most cases, the scale is caused by the formation of calcium and strontium carbonate and sulfate salts [1]. The consequences of scale deposition can be delayed production, failure of production equipment, unscheduled shutdowns, increased maintenance costs and decreased production efficiency [2].…”
Section: Introductionmentioning
confidence: 99%
“…Scale deposits could also plug the pores of the formation in injection wells, resulting in injectivity decline [3]. The scales commonly found in the deposit are carbonates [1,4]. While the formation of carbonate incrustations is associated with changes in pressure and temperature that favor precipitation of salts present in the water, the appearance of sulfate incrustations is mainly due to the mixing of incompatible waters to maintain pressure or to flooding strategies [2].…”
Section: Introductionmentioning
confidence: 99%